Perilaku Petani Anggota Subak Abian Ulun Desa dalam Budidaya Tanaman Kakao di Desa Bajera Utara, Kecamatan Selemadeg, Kabupaten Tabanan - SATRYASA, KADEK DWI SUPUTRA CANDRA; PUTRA, I GEDE SETIAWAN ADI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Behavior of the Abian Ulun Desa Subak Members in the Cocoa Cultivation in the Village of Bajera Utara, Sub-District of Selemadeg, Tabanan. Cocoa has been the main commodity of plantation sub-sector, and it has the potential to be developed in support of improving the income of farmers in Indonesia. Selemadeg sub-district is the center of the cocoa farmers in Tabanan, which in 2014, its productivity reached 1,659 kg/ha/year, but the productivity was not optimal considering the productivity of cocoa in Indonesia reached 2000 kg/ha/year. The low productivity of cocoa in several centers in cocoa production was estimated to be caused by the behavior of farmers in the cultivation of cocoa plants. The purpose of research was to study the behavior of the farmer members of Subak Abian Ulun Desa in the cultivation of cocoa plants. This research was conducted in the Subak Abian Ulun Desa, Village of Bajera Utara, Sub-District of Selemadeg, Tabanan. Subak of Abian Ulun Desa has the population of 46 people. Determination of respondents by using census method. The results showed the knowledge and attitudes of farmers in the cultivation of cocoa is classified as excellent category with the score of knowledge of 85.95% and the score of attitude of 87.09%. The lowest percentage was for the application of the farmers in the cultivation of cocoa plants that regarded as excellent category with a score of 84.69%. Behavior of farmers of Subak Abian Ulun Desa in the cultivation of cocoa plants considered as excellent category by achieving a score of 85.91%. Based on the research results, the behavior of farmers in the cultivation of cocoa plants need to be given training by the government, especially on the application of cultivation of cocoa to produce maximum cocoa production.
Keywords: behavior; cocoa plantation; subak; cultivation of cocoa